2015
DOI: 10.1021/acs.jpcc.5b01681
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1 nm Pd Nanoparticles in a Microfluidic Reactor: Insights from in Situ X-ray Absorption Fine Structure Spectroscopy and Small-Angle X-ray Scattering

Abstract: A novel microfluidic reactor for in situ small-angle X-ray scattering (SAXS) and X-ray absorption fine structure spectroscopy (XAFS) of Pd colloidal nanoparticles synthesis is reported. The microreactor allows time resolution ranging from milliseconds to several minutes with a residence time of over an hour. The synthesis of colloidal Pd nanoparticles is investigated in the presence of oleylamine and trioctylphosphine ligands. For both ligands, SAXS results show the synthesis proceeds through slow, continuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
86
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 81 publications
(118 reference statements)
2
86
1
Order By: Relevance
“…The variations in the XANES spectra, observed in Figure , clearly show the dependence of the Pd 2+ ligand exchange on the amount of KI. This allowed us to perform linear combination analysis (LCA) using as‐prepared PdI 2 ‐NPs and Pd(OAc) 2 as standards (inset in Figure ).…”
Section: Figurementioning
confidence: 99%
“…The variations in the XANES spectra, observed in Figure , clearly show the dependence of the Pd 2+ ligand exchange on the amount of KI. This allowed us to perform linear combination analysis (LCA) using as‐prepared PdI 2 ‐NPs and Pd(OAc) 2 as standards (inset in Figure ).…”
Section: Figurementioning
confidence: 99%
“…In situ measurements allow for information at different stages in both time and space during synthesis or activity testing of catalyst materials. With this information, the growth rate, reaction intermediates and deactivation can be monitored 26,53,57,62,[108][109][110][111][112] allowing for kinetic and mechanistic studies, 108,[113][114][115][116][117] as summarized in Table 4 and illustrated in Fig. 3.…”
Section: Introductionmentioning
confidence: 99%
“…First, characterization techniques used in microfluidics will be discussed. Second, direct characterization of NPs will be discussed, where the characterization of the shape, size, oxidation state, crystal structure and elemental composition is analysed, 26,53,57,62,[118][119][120][121] as can be found in Fig. 3.…”
Section: Introductionmentioning
confidence: 99%
“…Microreactors offer a small volume for the reaction, which allows precise control over the synthesis of nanoparticles such as palladium (Pd), platinum (Pt) and gold (Au) etc. [16][17][18]. Rebrove et al [19] have shown that a microreactor system increases the heat transfer within the reaction mixture and hence improves the reaction kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…It has more oxidation potential than Pt [2,30]. Pd is suitable for hydrogen storage and sensing applications [31].There are several methods available for synthesizing Pd nanoparticles using precursors such as palladium chloride (PdCl 2 ), potassium tetrachloropalladates (K 2 PdCl 4 ),palladium nitrate, palladium acetate with reducing agents such as hydrogen, ethylene glycol, NaBH 4 , xanthan gum, hydrazine, alcohol, sodium ascorbate and sodium citrate and along with capping agents such as cetyl trimethylammonium bromide (CTAB), polyvinylpyrrolidone (PVP) and sodium dodecyl sulfate (SDS) [32][33][34][35][36][37][38][39][40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%